(untitled) (Journal of Medical & Health Sciences Review, 2025)
Postpartum low back pain (LBP) represents a significant yet often overlooked maternal health concern, particularly in regions where sociocultural factors heavily influence healthcare behaviors. This narrative review examines the complex interplay between traditional beliefs and postpartum LBP management in Balochistan, Pakistan - a region characterized by strong cultural traditions and limited healthcare access. Through analysis of existing literature and local health practices, we explore how cultural norms such as postpartum seclusion (Chilla), gender roles, and traditional healing methods shape women’s experiences of LBP. The review identifies key barriers to effective pain management including restricted mobility during Chilla, rapid return to domestic duties, reliance on traditional therapies, and limited access to biomedical care. We propose culturally-adapted solutions that bridge traditional and evidence-based approaches, emphasizing community engagement and health system strengthening. This review highlights the urgent need for interventions that respect local traditions while improving pain management outcomes for postpartum women in Balochistan and similar cultural contexts.